Single rhodium atoms anchored in micropores for efficient transformation of methane under mild conditions - Yu Tang (Nature Portfolio, 2018)
Catalytic transformation of CH4 under mild conditions has implications to shale gas utilization. Here, the authors report the transformation of CH4 to acetic acid through coupling of CH4, CO and O2 on single-site Rh1O5 anchored in microporous aluminosilicates in liquid phase.